Age related structural and functional changes in left ventricular performance in healthy subjects: a 2D echocardiographic study - Vriz, Olga; Pirisi, Mario; Habib, Eiad; Galzerano, Domenico; Fadel, Bahaa; Antonini-Canterin, Francesco; Veldtman, Gruschen; Bossone, Eduardo (The International Journal of Cardiovascular Imaging, 2019)
Left ventricular (LV) adaptation to aging is currently poorly understood. We aimed to characterize age related changes in LV structure and function by studying a large group of healthy subjects across a wide age range. Prospectively enrolled healthy volunteers (n = 778, 327 females; age 18 to 100 years, mean age 49.8 ± 18.1 years), were divided into 4 age groups: 18 to 34 years (n = 165); 35 to 49 years (n = 242), 50 to 79 years (n = 334) and ≥ 80 years (n = 40). All subjects underwent clinical examination, as well as comprehensive transthoracic echocardiogram [TTE]. Body mass index, systolic blood pressure (BP), and left atrial volume (p < 0.0001) increased with age while diastolic BP (p < 0.0001) decreased over time. LV mass/body surface area (BSA) and relative wall thickness increased with age (p < 0.0001) coincident with worsening parameters of diastolic function (E/A and E/Em, p < 0.0001). The ejection fraction and Sm did not change significantly. Stroke volume, ejection time index, flow rate and stroke work significantly increased with age (p < 0.01). The arterial elastance (Ea), a measure of ventricular afterload, and ventricular elastance (Ees), an index of LV systolic stiffness did not change with age nor did their ratio (Ees/Ea) the latter being an expression of ventricular-arterial coupling. Age, gender and LVM were the main independent variables associated with LV systolic function. In conclusion, LV adaptation to aging in a healthy cohort is characterized by concentric LV remodeling, increased contractility and preserved ventricular-arterial coupling.